The Routledge atlas of the first world war - Gilbert, Martin, 1936-2015, author.
1 online resource.
Keywords: "The Routledge Atlas of the First World War From its origins to its terrible legacy, the tortuous course of the Great War is vividly set out in a series of 174 fascinating maps. Together the maps form a comprehensive and compelling picture of the war that shattered Europe, and illustrate its military, social, political and economic aspects. Beginning with the tensions that already existed, the atlas covers: Section depicting the visual remembrance of the war; a fascinating visitors' guide to the memorials that commemorate the tragedy of the Somme. This new edition now includes an additional 37 of Martin Gilbert's maps, across the whole period of the war, originally published across a range of publications, now gathered in this one volume for the first time"--